Controlling supramolecular chirality in multicomponent self-assembled systems - Xing, Pengyao (2020)
Chirality exists as a ubiquitous phenomenon in nature, from molecular level l-amino acids, d-sugar, secondary structures of proteins, DNA, RNA, and nanoscale helices to macroscopic conch and even galaxy. The aggregation of molecular building blocks with or without chiral centers might bring about asymmetric spatial stacking, which further results in the appearance of nonsymmetry in extended scales like helical nanofibers. This phenomenon, known as supramolecular chirality, is an important branch of supramolecular and self-assembly chemistry, which relates intimately with biomimetics, asymmetric catalysis, and designing chiroptic advanced materials. One of the important research focuses among supramolecular chirality is about rational manipulation of chirality amplification and handedness, presenting a profound influence on the performance of resulting soft materials such as circularly polarized luminescence and cell adhesion on hydrogels. The control over supramolecular chirality normally relies on two factors, i.e., thermodynamic and kinetic variables dependent on molecular structural parameters and environmental contributions, respectively. Supramolecular chirality in two or more component-based systems places an emphasis on thermodynamic control as it occurs from either integrated coassembly or separated self-sorting, which is more sophisticated than that of single component systems. Thus, the study on supramolecular chirality in multicomponent systems could mimic complicated biosystems, allowing for better understanding about the origin of natural chirality and extended applications as biomimetics. To date, the exploration of supramolecular chirality in multicomponent systems is restricted on both fundamental and application aspects when compared to more matured single component systems. Over the past few years, we have carried out systematic studies on several systems expressing supramolecular chirality from chiral amplification or symmetry breaking. We emphasized more the thermodynamic control by introducing a second component to form noncovalent bonding like hydrogen bonding or coordination interactions. In this Account, we would specifically discuss rational manipulation of the occurrence, transfer, and inversion of supramolecular chirality by taking several of the latest representative examples. In the multicomponent systems, in addition to the building blocks with chiral centers, the second or third components could be structural analogues and achiral small molecules such as bipyridines, melamine, metal ions, inorganic nanomaterials, and even solvents. These second or third components are able to incorporate during the aggregation to form coassembly via noncovalent bonds, influencing spatial arrangements of building blocks within various dimensions from vesicles and nanofibers to organic/inorganic hybrids. Other than chirality, morphology, stimulus responsiveness, and properties could also be well tailored by controlling interactions between different components.